Comparative Analysis on Special Quality Control of Malignant Tumor Medical Record. (April 2014) - Peng, Ye; Zhang, Xugang; Han, Yichao; Xie, Na; Yang, Xiufang; Zhang, Xiuyan
Abstract: Objective . To know the problems in medical record writing and diagnosis and treatment through the quality control of the malignant tumor medical records, identify the causes, and formulate measures for improvement, to standardize the diagnosis and treatment of malignant tumors. Methods. A total of 500 discharge malignant tumor medical records from June to August 2012 and 500 discharged malignant tumor medical records from June to August 2013 are randomly selected. The medical record quality control experts use a "special quality control table of malignant tumor" for quality control and statistical analysis. Results . After special medical record quality control, the defect rates of eight items, namely the diagnostic basis, name of the disease diagnosed, therapeutic scheme, pathological report, image report, informed consent, doctor's advice upon discharge and disease coding, are obviously reduced ( P = 0.00) in the malignant tumor medical records, compared with those before quality control. Conclusion. Through the special quality control of the malignant tumor medical records, defective medical records are significantly reduced, and the diagnosis and treatment of malignant tumors is standardized.